NUMERICAL SIMULATION OF NON – UNIFORM CORROSION INDUCED CRACKING - Sylviah Rizky Novia Anwaari; Harun Alrasyid; Wahyuniarsih Sutrisno (Journal of Civil Engineering, 2022)
This research is focused on modeling the damage of concrete due to corrosion. The load used in this paper is only focused on the internal load due to rust expansion. In this study, corrosion was modeled uniformly and non-uniformly to investigate the difference between these two configurations to the damage in concrete. The simulation in this study was carried out using the 3DNLFEA program. The results show that numerical simulation provides predictions that are in line with experimental and numerical modeling results performed by the previous study in terms of pressure and corrosion cracking patterns. From the crack analysis, the pattern found that a non-uniform corrosion model can be used to express a realistic rust corrosion development around the reinforcement. Meanwhile, uniform corrosion requires a larger loss of steel area to reach the damage stage. Therefore, for non-uniform corrosion, the corrosion rate cause cracks and reaches a limiting crack width at earlier times in the service life of the corroded part.